Peran Kelembagaan Bank Sampah Nawasena Kemala sebagai Penguat Ekonomi Masyarakat Desa Daleman Kidul - Fitriana, Yenny Reiza; Hapsari, Salsabila Nur; Hartono, Budi; Robbani, Hamzah (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
This service is an output of activities from the Ministry of Education and Culture, Research and Technology's Belmawa grant funding to PPK Ormawa HMJM Tidar University. This service activity aims to improve the quality of organic and non-organic waste processing in Daleman Kidul Village, Pakis District, Magelang Regency. The method for implementing PPK Ormawa HMJM UNTIDAR service activities is in the form of training and counseling, as well as the establishment of institutions at the village level to create sustainability of the waste processing program. The objects of this activity are residents' agricultural waste, residents' kitchen waste, and plastic waste which can still be used as handicrafts, while residual waste is collected for collective processing at the Magelang Regency Environmental Service. Internal partners involved in this activity include the Village Head, Village Secretary, Kadus, Babinsa, Bhabinkamtibnas, Tomas, religious figures. PKK mothers and Karangtaruna. Meanwhile, external partners in this activity include academics across universities in Magelang Regency, Bappeda Litbangda Magelang Regency,MySmash app, and various Department elements within the Magelang Regency Government. The tools and materials used are a set of tools for cultivating maggots, a shelter for making compost fertilizer, and supporting tools for making handicrafts. The result of this service activity is the organized handling of both organic and non-organic waste banks, as well as increasing public awareness in managing waste into economically valuable products.